GAMBARAN KECEMASAN MAHASISWA YANG MELAKUKAN PRAKTEK KLINIK DI RUMAH SAKIT PADA MASA PANDEMI COVID 19 - Nanang Khosim Azhari; Tuti Anggarawati; Fitriana Noor S; Prestiyana A K (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2021)
The prevalence of the disease caused by the corona virus is still increasing every day. On August 11, 2020, the World Health Organization (WHO) recorded 19,936,210 people infected with the corona virus and 732,499 people who died, the death rate reached 3.7% 4. In Indonesia, the number is still actively increasing every day, ranging from 1,000 people. every day in August 2020 and the total number of COVID-19 sufferers on August 11, 2020 was 128,776 people and 5,824 people died, an increase of 4.5% from the previous number 5. Central Java Province itself was ranked 4th out of all provinces in Indonesia with the number of patients with Cobid 19 as many as 11,423 people and those who died as many as 1,049 people. The city of Semarang is ranked 1st out of cities and regencies in Central Java Province with 661 sufferers